Dynamics of firm competitive advantage in emerging industries: Cases of China’s shared cycle industry and mobile battery sharing industry - Yanpeng SUN (AAOS Transactions)
Using the case studies of China’s shared bicycle and mobile battery-sharing industries, this report examines how late entrants reversed leading firms that gained a competitive advantage in emerging industries. The first entrant gained a competitive advantage in both industries by quickly occupying the first-tier city market. However, the rise of second-tier and lower-tier city markets has led to a phenomenon where the first entrant has been overtaken by a late entrant that has consolidated its position in the second-tier and lower-tier cities. This report traces the behavior of each player in the two industries over time and analyzes each player’s learning in different markets and its response to changes in the market environment. The analysis revealed that under market uncertainty, although the market entered by the late entrant grew to become the main market, the resources and capabilities accumulated by the early entrant in the market were not adaptable to the market entered by the late entrant, resulting in the late entrant overtaking the early entrant.